The Internationalization of Chinese Firms and Negative Media Coverage: The Case of Geely's Acquisition of Volvo Cars. (20th April 2017) - Fang, Tony; Chimenson, Dina
Abstract : Chinese firms are internationalizing at an unprecedented speed. One profound phenomenon linked to this active Chinese firms internationalization process is that the process tends to be confronted with negative media coverage of China and Chinese firms in Western countries. How to understand and cope with the negative image of China and Chinese firms, as they are often seen in the Western media, emerges as a relevant and timely research topic in the study of the internationalization of Chinese firms. The purpose of this article is to stimulate ideas for further research on the relations between the internationalization of Chinese firms and the media coverage. We use the case of Geely's acquisition of Volvo Cars, which was to a large extent negatively reported in the Swedish media during 2008–2013, as inspiration to identify the interesting research themes and questions. Given the increasing anti‐globalization trend, we hypothesize that Chinese firms will have to face up to the reality of negative media coverage in many Western countries for the foreseeable future, at least in the firms' initial establishment phases. We end our paper with the managerial implications. © 2017 Wiley Periodicals, Inc .